Možnosti rozboru důchodové situace domácností na regionální úrovni - Jana Stávková (Trendy Ekonomiky a Managementu, 2013)
Purpose of the article: The paper deals with issue of evaluation of population’s income situation when selected segmentation criteria have been applied. Methodology/methods: Data for the analysis was gained from a national module of the EU-SILC project. Period chosen was year 2008 which is considered a milestone in the national economic development. The basic variable in calculations was the income level of household. The average monthly income per household member was obtained by dividing the reported disposable household income by number of household members. The number of households at risk of income poverty and the depth of poverty indicators were calculated. Subsequently a quantile analysis was performed and Gini coefficients were calculated. The criterion used was the geographical division of the Czech Republic to regions according to the Standardized classification of territorial units (CZ-NUTS). Region analyzed was Zlín Region. Scientific aim: The aim was to propose a methodological procedure for carrying out the income situation evaluation. The procedure should enable a derived research on income situation and represent a tool that could support creation and direction of the social policy. Findings: Findings of the regional analysis were the lag of disposable income in the region behind the national average, more than twice the share of households at risk of income poverty and uneven representation in income quintiles (in favor of the lowest quintile). The value of the Gini coefficient for the region was 0,210, which indicated a slightly more balanced diversification of incomes compared to the national average (Gini 0,228). Conclusions: The lower value of the Gini coefficient indicated a relatively higher potential of stability of the region. However, summarizing the results authors concluded that long-term structural problems of the region were identifiable and negatively reflected in the income situation of its inhabitants.